Photoallergies - Śpiewak, Radosław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Photoallergic diseases – solar urticaria and photoallergic contact dermatitis – are encountered in every allergist’s practice. Unfortunately, most such cases are treated non-specifically as “sun allergy” and remain undiagnosed. Focused diagnostic procedures – photoprovocation and photopatch testing – would enable the managing physician to find the actual cause and select the most adequate treatment. Solar urticaria (SU) is an IgE-dependent photoallergic disease. The suspicion of SU should always be taken into account when the following features are observed: 1) development of pruritus, erythema and wheals on the sun-exposed skin, 2) appearance of the symptoms within minutes after sun exposure, 3) spontaneous resolution within a few hours. The diagnostics is based on photoprovocation with suspected allergens and autologous serum. The treatment of SU includes: avoidance of the allergen in exogenous variant of SU, avoidance of the provoking radiation type, and antihistamines (effective in 2/3 cases). Photoallergic contact dermatitis (PhotoACD) belongs to the Gell & Coombs type IV allergic reactions. Inflammatory skin diseases appear 24-48 h after exposure, and are limited to skin areas exposed to both the sensitizing photohapten and the irradiation. The final diagnosis requires photopatch testing, in which series of test substances are applied in double. After 48 h, one of the series is irradiated, typically with 5 J/cm 2 UVA. Therapy of PhotoACD comprises avoiding the responsible photohaptens. Photoprotection may be very helpful, but some patients may be photosensitized to sunscreens. Therefore, photopatch testing is recommended with ingredients of sunscreens while selecting the proper photoprotection. Pharmacological therapy of PhotoACD follows the same rules as “classical” allergic contact dermatitis, and is mainly based on topical corticosteroids, calcineurin inhibitors, and barrier creams. Antihistamines are ineffective in photoallergic eczema.